Work-Life Balance, Happiness at Work, and Employee Performance: The Mediating Role of FRMS at Perum LPPNPI Denpasar - Pradita Jaya, I Putu Surya; Putu Kawiana, Prof. Dr. I Gede; Yayati Wilyadewi, Dr. Ida I Dewa Ayu (Langit Biru: Jurnal Ilmiah Aviasi, 2025)
This study aims to analyze the influence of Work-Life Balance and Job Happiness on employee performance, mediated by the Fatigue Risk Management System (FRMS), with a case study at the operational employees of Perum LPPNPI Denpasar Branch. The study uses a quantitative descriptive approach, involving proportional sampling and distributing questionnaires to operational staff. The results show that Work-Life Balance and Job Happiness significantly influence employee performance, meanwhile the FRMS unable to stand as a mediating variable. Proper implementation and evaluation of FRMS should be applied to strengthens the influence of WLB and Job Happiness on performance. The implication of this research is the importance of managing work-life balance and fatigue risks for improving the operational employee performance.